Tonsillectomy Outcomes in Children After Solid‐Organ Transplantation: A 15‐Year Single‐Center Experience. (19th January 2023) - Hazkani, Inbal; Hajnas, Natalia; Victor, Mitchell; Stein, Eli; Richardson, Aida; Billings, Kathleen R.
Abstract: Objective: Solid‐organ transplantation (SOT) has become the standard of care for children with terminal organ failure. Long‐term immunosuppression has improved survival substantially but is associated with secondary malignancies and impaired wound healing. Our goal was to review the incidence, outcomes, complications, and rate of posttransplant lymphoproliferative disorder on pathologic examination following tonsillectomy/adenotonsillectomy (T/AT) in children after SOT. Study Design: A retrospective cohort study. Setting: Tertiary care children's hospital. Methods: Data were extracted from charts of children with a history of kidney, heart, or liver transplantation, who underwent T/AT between 2006 and 2021. Results: A total of 110 patients met the inclusion criteria, including 46 hearts, 41 kidneys, 19 livers, and 4 liver‐and‐kidney transplants. The mean age at transplantation was 4.2 years, and the mean transplantation‐to‐T/AT time interval was 28.8 months. The posttransplant lymphoproliferative disorder was diagnosed in 52 (47.3%) patients, and 25% of these had no tonsillar hypertrophy. There was no difference in age at transplantation, organ received, transplantation‐to‐T/AT time interval, immunosuppressive medications, tonsil size, or tonsillar asymmetry between patients diagnosed with the posttransplant lymphoproliferative disorder and patients with benign tonsillar/adenotonsillar hypertrophy. Posttonsillectomy complications were similar between the groups. Conclusion: The incidence of posttransplant lymphoproliferative disorder undergoing tonsillectomy for any indication was 47.3%. There was no association between preoperative signs and symptoms and the histopathological diagnosis of posttransplant lymphoproliferative disorder. Stratification by organ received and immunosuppressive medications did not identify differences among the groups relative to the incidence of posttransplant lymphoproliferative disorder and other postoperative complications.